ЎҚУВ ЛУҒАТЛАРИ ОРҚАЛИ БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИНИНГ НУТҚИЙ КОМПЕТЕНЦИЯСИНИ РИВОЖЛАНТИРИШ - Кожалепесова, П.А. (SCIENCE and SOCIETY, 2025)
The article examines the impact of using various types of educational dictionaries on the development of speech in young schoolchildren. The research results show that orthographic, pronunciation, explanatory, pictorial, and digital dictionaries have a positive impact on language proficiency levels, help develop correct pronunciation, and improve spelling skills. Also, methods for the appropriate implementation of these manuals in the educational process have been created, taking into account the requirements of modern knowledge assessment systems and domestic pedagogical experience, with the aim of strengthening the speech skills of primary school students.
Keywords: educational dictionary; spelling; pronunciation; orthoepy; orthography; speech competence; explanatory dictionary; illustrative dictionary; multimedia dictionary